A surprising spat: The causes and consequences of the Saudi–Canadian dispute. (June 2019) - Juneau, Thomas
In August 2018, Saudi Arabia expelled the Canadian ambassador to Riyadh, recalled its own ambassador in Ottawa, and imposed sanctions on Canada. This overreaction to tweets by the Canadian foreign ministry demanding the release of jailed activists was consistent with the pattern of foreign policy assertiveness that has accompanied the rise of Mohammed bin Salman (MbS). The Saudi–Canadian spat is not very important: bilateral ties were never essential for either country. But the dispute carries lessons for Canada and its allies as they reflect on future ties to the Kingdom. This partnership was always necessary but costly. MbS, however, has amplified and exposed these costs. By bringing unprecedented scrutiny to Saudi actions, recent events have opened a window of opportunity for Canada and its allies to re-evaluate relations. They should increase pressure on Riyadh to change the costliest aspects of its policies. Should this fail, they should downgrade the partnership.